Integrasi Dialog Budaya dalam Pendidikan untuk Menanamkan Nilai Keberagaman Budaya Nagekeo - Klemens Mere (Yayasan Riset dan Pengembangan Intelektual, 2025)
Cultural diversity is a vital foundation of Indonesian social life, yet it must be continuously nurtured through education so it becomes a lived value rather than a slogan. This literature review examines how cultural dialogue can be integrated into educational practices to instill respect for cultural diversity, specifically within the context of Nagekeo. Synthesizing studies published from 2020 onward, the review highlights key forms of integration such as dialogic pedagogy in the classroom, contextual learning grounded in local wisdom, intercultural projects, and active collaboration with families and traditional cultural actors. The reviewed literature consistently shows that cultural dialogue is most effective when designed as an interactive, reflective process that invites students to share experiences, negotiate meanings, and learn from differences. In Nagekeo, cultural dialogue can be strengthened through local narratives, customary rituals, language practices, and communal traditions that connect school learning with everyday cultural realities. However, implementation faces challenges including limited teacher capacity to facilitate intercultural dialogue, the marginal position of local culture in formal curricula, and the risk of superficial cultural activities without deep reflection. The review concludes that sustainable integration requires curriculum alignment, teacher training, and long-term partnerships between schools and the Nagekeo community to make cultural diversity education authentic and transformative.